LITERASI KEUANGAN DIGITAL SEBAGAI UPAYA PENDUKUNG PEREKONOMIAN - Ciptawaty, Ukhti; Wahyudi, Heru; Andrian, Thomas; Wiryawan, Driya; Usman , Moneyzar (Faculty of Economics and Business Lampung University, 2023)
Kurungan Nyawa Village in Pesawaran District shows signs of weakness in BUMDes management. The implementation of BUMDes in Kurungan Nyawa Village is constrained by three main problems, namely economic, social, and human potential issues. Academics who can help improve the management and administration of BUMDes business units that are not producing at peak production levels, even in a state of suspended animation, can help solve three problems faced by BUMDes in Kurungan Nyawa Village, Pesawaran Regency.